Mucosa-Associated Lymphoid Tissue Lymphoma of the Larynx - Omar Rizvi; Tyson Nielsen; Shethal Bearelly (Case Reports in Otolaryngology)
Background. Mucosa-associated lymphoid tissue (MALT) lymphomas are a subtype of non-Hodgkin lymphoma stemming from marginal zone B-cells. In this case report, we present two patients with an extremely rare localization of MALT lymphoma to the larynx. Methods. Case 1 is of a 78-year-old male presenting with a six-month history of progressive hoarseness with a past medical history significant for marginal zone lymphoma of the right orbit. Diagnosis was confirmed with a biopsy for extranodal marginal zone B-cell lymphoma of MALT type. An FDG-PET scan was done but did not show any sign of FDG avid malignancy, including at the primary site. Case 2 is a 60-year-old female presenting with one year of worsening throat discomfort, intermittent cough, and dyspnea with exertion. Pathology confirmed a diagnosis of extranodal marginal zone B-cell lymphoma of MALT type. Results. Case 1 was treated with low-dose radiation at 4 Gy delivered over two fractions of 2 Gy each. Upon completion of radiation treatment, he reported a resolution of his hoarseness and normalization of his voice. A four-month follow-up in May 2018 with flexible nasolaryngoscopy revealed a normal exam with fully mobile vocal folds bilaterally and no evidence of left false vocal fold submucosal mass. At seven months following treatment, the patient died unexpectedly of unknown causes. Case 2 was treated with radiation at 30 Gy in 15 fractions over the course of one month. Following completion of radiation therapy, she had improvement of her sore throat, nausea, dysphagia, dysgeusia, and dry mouth. At 21-month follow-up, she had no evidence of disease. Conclusion. This case report demonstrates that MALT lymphoma can present with much more benign and subtle symptoms. This highlights the importance of clinicians to keep broad differentials and consider MALT lymphomas in the setting of laryngeal masses.